Nickel foam supported porous copper oxide catalysts with noble metal-like activity for aqueous phase reactions. Issue 12 (13th April 2022) - Shultz, Lorianne R.; Preradovic, Konstantin; Ghimire, Suvash; Hadley, Hayden M.; Xie, Shaohua; Kashyap, Varchaswal; Beazley, Melanie J.; Crawford, Kaitlyn E.; Liu, Fudong; Mukhopadhyay, Kausik; Jurca, Titel
Abstract : Metal foams offer numerous advantages over powders as supports for nanostructured heterogeneous catalysts; most critically a preformed 3-D porous framework ensuring full directional coverage of catalyst, intrinsic ease of handling and recyclability. Abstract : Contiguous metal foams offer a multitude of advantages over conventional powders as supports for nanostructured heterogeneous catalysts; most critically a preformed 3-D porous framework ensuring full directional coverage of supported catalyst, and intrinsic ease of handling and recyclability. Nonetheless, metal foams remain comparatively underused in thermal catalysis compared to more conventional supports such as amorphous carbon, metal oxides, zeolites and more recently MOFs. Herein, we demonstrate a facile preparation of highly-reactive, robust, and easy to handle Ni foam-supported Cu-based metal catalysts. The highly sustainable synthesis requires no specialized equipment, no surfactants or additive redox reagents, uses water as solvent, and CuCl2 (H2 O)2 as precursor. The resulting material seeds as well-separated micro-crystalline Cu2 (OH)3 Cl evenly covering the Ni foam. Calcination above 400 °C transforms the Cu2 (OH)3 Cl to highly porous CuO. All materials display promising activity towards the reduction of 4-nitrophenol and methyl orange. Notably, our leading CuO-based material displays 4-nitrophenol reduction activity comparable with very reactive precious-metal based systems. Recyclability studies highlight the intrinsic ease of handling for the Ni foam support, and our results point to a very robust, highly recyclable catalyst system.